The Aesthetic Components of Realism and Its Reflection in Several Paintings by Gustav Korbe - Ahmad Mohammadi; Hosein Ardalani (هنر اسلامی, 2019)
Realism as a trend in the art of painting declared its presence in the first and second decades of the nineteenth century. The founder of this artistic genre was French painter Gustav Corbé. Artists of Realism break the eternal rules of the artists of their time and focus on everyday issues, social excitement, critic the upper classes of society an ultimately reflect the lives of people destitute of romantic dreams and exaggerations build their aesthetic components and through this community-oriented tendency, they encounter the popular appeal of the audience. In the sense of the objectivist and societal nature of realism, its vibrant attitude has continued and sustained until contemporary times. From this point of view, the study of the aforementioned aesthetic elements, especially in the art of painting, and its reflection in the works of Gustav Corbé, has the potential to raise the aesthetic features of realism more than the aesthetic elements of contemporary abstract painting. Writings of this kind can provide a suitable context for art lovers to appreciate and encounter modern artworks. In this paper, while introducing a history of realism and expressing its aesthetic coordinates, we attempt to highlight some of the most prominent works of Gustav Korbe paintings, including "Crusaders", "Burial in Uranus" and "Ladies of the Village" from the viewpoint of aesthetic components of the realistic trend